2019
DOI: 10.1155/2019/9713189
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Oblique Muscle Overaction: Clinical Features and Surgical Management

Abstract: Purpose. To further define the clinical features of patients with inferior oblique muscle overaction (IOOA) and evaluate the surgical results in a subgroup of these patients. Methods. The medical records of 173 patients who underwent inferior oblique muscle (IO) weakening surgery due to primary or secondary IOOA were retrospectively reviewed. The patients were assigned a surgical group based on severity of IOOA and presence of dissociated vertical deviation (DVD) or hypertropia. Patients with +1 or +2 IOOA und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…They concluded that no significant difference was found between the two groups; however, bilateral surgery had a higher rate of causing IO undercorrection. E M Helveston reported that contralateral IOOA was aggravated postoperatively with unilateral IO weakening [ 9 ]. Manal Kasem et al reported that 66.6% of patients with unilateral IOOA developed contralateral IOOA in the myectomy group ( P < 0.001) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that no significant difference was found between the two groups; however, bilateral surgery had a higher rate of causing IO undercorrection. E M Helveston reported that contralateral IOOA was aggravated postoperatively with unilateral IO weakening [ 9 ]. Manal Kasem et al reported that 66.6% of patients with unilateral IOOA developed contralateral IOOA in the myectomy group ( P < 0.001) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costenbader FD et al analyzed three different IO weakening procedures and suggested that the effects of myotomy at its origin, recession at the scleral insertion and partial myectomy were similar [ 8 ]. Ercan Ozsoy et al studied the efficacy of IO weakening treatment in 179 patients with IOOA and showed that the cure rates of IO recession, myectomy and anterior transposition were 96%, 98.4% and 93.9%, respectively [ 9 ]. Antielevation syndrome was found in patients with IOOA who underwent IO anterior transposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these procedures are also intended to correct the primary gaze hypertropia as well as excyclotorsion. [1][2][3][4][5][6][7] In clinics, the inferior oblique muscle overaction is frequently encountered in infantile esotropes, where it can be witnessed in up to 70% of the cases, 1 such overactions can also be witnessed in superior oblique palsy, comitant horizontal deviations, dissociated vertical deviation, and others. To treat it, in milder grades (usually 1+), we prefer 8-10 millimeters of inferior oblique recession, and in grade 2+ we prefer 12-14 millimeters of recessions or Elliott and Nankins procedure.…”
Section: Introductionmentioning
confidence: 99%
“…All these techniques are able to cure the over-elevation in adduction, and also they are able to collapse the associated "V" pattern strabismus, 1,5,7 however, the anteriorization procedures are quite famous for their anti-elevation effect, or the antielevation syndrome (as described by Kushner). 9,10 Where, due to anatomical changes in the inferior oblique muscle course and its associated neurovascular bundle the vertical rotation is limited, clinically, it can be witnessed as elevation deficit in abduction as well as in primary gazes (Figure 1).…”
Section: Introductionmentioning
confidence: 99%